Translanguaging as a pedagogical strategy to implement multilingual language policy at a South African university - Motaung, Brakpan Letsela (University of the Free State, 2021)
South African institutions of higher learning continue to grapple with the practical implementation of language policies. Universities have amended their policies to adhere to the language policy for higher education and others have shown progress in their implementation strategies. However, a recent report from the minister of DHET has shown that universities have not implemented their language policies as guided by the constitution and other promulgated policies in higher education terrain. In tandem, in recent times, translanguaging as a pedagogical strategy has been gaining momentum in the higher education space. Various studies have reported its benefits and limitations in the education sector. Against the foregoing policy and pedagogy backdrop, this study explored the use of translanguaging as an alternative pedagogical strategy to implement multilingual language policy in undergraduate tutorials. Tutors and students were invited to participate in this study. The theoretical approaches which guided the study were Orientations in Language Planning and Culturally Sustaining Pedagogy. Data was generated through semi-structured interviews and focus group discussions. Data analysis was done through thematic analysis. Findings indicate that translanguaging as pedagogical strategy has the potential to leverage implementation of multilingual language policy, when deployed strategically, this implies the necessity to assess the on current challenges and future of multilingual practices. Findings further show that translanguaging assists both tutors and students to make sense of their learning and understanding of the content, promotion of indigenous languages, decolonization and student engagement within tutorials. The study concluded that translanguaging as a pedagogical strategy create a space for both tutors and tutees to use their linguistic repertoires in a multilingual classroom. In addition, translanguaging as a pedagogical strategy is helpful in responding to the contemporary multilingual language policy conundrums in higher education. In conclusion, the study recommends ways in which translanguaging could be employed to implement multilingual language policy in the tutorials within the higher education space in South Africa, and possibly elsewhere.
Dissertation (M. A. (Higher Education Studies))--University of the Free State, 2021
Keywords: Translanguaging; Multilingual language policy; South African university; Undergraduate tutoring